2018
DOI: 10.5380/ce.v23i2.52774
|View full text |Cite
|
Sign up to set email alerts
|

Prática Baseada Em Evidência No Contexto Dos Núcleos De Apoio a Saúde Da Família Em Chapecó Apoio a Saúde Da Família Em Chapecó

Abstract: Objetivo: analisar a Prática Baseada em Evidência no trabalho dos profissionais da equipe do Núcleo de Apoio à Saúde da Família. Método: estudo descritivo realizado no município de Chapecó - Santa Catarina. A população do estudo foi composta de 28 profissionais que atuavam nos núcleos, no ano de 2016. A análise dos dados ocorreu por estatística descritiva. Resultados: os profissionais destacaram dificuldades em converter as necessidades de conhecimento em questão de pesquisa, mas se disseram aptos para levanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
0
0
4
Order By: Relevance
“…It has been suggested that there is little evidence-driven practice regarding its effectiveness in coping with OW and highly dependent on empiricism of accumulated experiences. A similar result was found in a study on Evidence-Based Practice (EBP) of NASF professionals in the city of São Paulo revealed that, although professionals recognize the importance of EBP, the daily routine of service is still focused on the clinical experience and, to a lesser extent, on scientific evidence and preference for individual care [22]. Practice poorly guided by scientific evidence often leads to failure of professionals when addressing overweight individuals, such as temporary change in eating habits, limited weight loss, discontinuity, frustration and anxiety -as identified in the "emotions" domain of the "motivation" component.…”
Section: Emotionssupporting
confidence: 74%
“…It has been suggested that there is little evidence-driven practice regarding its effectiveness in coping with OW and highly dependent on empiricism of accumulated experiences. A similar result was found in a study on Evidence-Based Practice (EBP) of NASF professionals in the city of São Paulo revealed that, although professionals recognize the importance of EBP, the daily routine of service is still focused on the clinical experience and, to a lesser extent, on scientific evidence and preference for individual care [22]. Practice poorly guided by scientific evidence often leads to failure of professionals when addressing overweight individuals, such as temporary change in eating habits, limited weight loss, discontinuity, frustration and anxiety -as identified in the "emotions" domain of the "motivation" component.…”
Section: Emotionssupporting
confidence: 74%
“…Do mesmo modo mostram os resultados de um estudo com os profissionais da equipe do Núcleo de Apoio à Saúde da Família (NASF), que informaram estarem aptos para levantar evidências científicas e identificar os principais tipos e fontes de informação existentes. Entretanto, há obstáculos para o desenvolvimento da prática baseada em evidência, tais como a elevada carga de trabalho e a falta de incentivo dos gestores 27 .…”
Section: Autoria Título Objetivo Tipo De Tecnologiaunclassified
“…O impacto positivo de facilitar o acesso a informações de SBE contribui diretamente com o aumento da conscientização e, consequentemente, a prática profissional melhora na assistência aos pacientes, uma vez que o conhecimento científico, com uma linguagem mais democrática, proporciona uma melhor compreensão para os profissionais e, assim, estes passam a sentirem-se mais confortáveis e confiantes para a prestação de cuidados de saúde com qualidade 17,25 .…”
Section: Como Citar Este Artigounclassified